2009
DOI: 10.1080/03630240903158446
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' and Women's Views on Hormone Therapy and Breast Cancer Risk After the WHI: A Qualitative Study

Abstract: Our qualitative study suggests that after the Women's Health Initiative, concerns about breast cancer risk weighed into decisions to initiate and continue hormone therapy for both physicians and women, but menopausal symptoms often directed use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…There was good (κ = 0.64) agreement between MFT and YCT on choosing the final 77 applicable full-text studies for potential inclusion. Of these studies, 40 were excluded for various reasons, leaving 37 studies [5], [7], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62] included in our analyses (See figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was good (κ = 0.64) agreement between MFT and YCT on choosing the final 77 applicable full-text studies for potential inclusion. Of these studies, 40 were excluded for various reasons, leaving 37 studies [5], [7], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62] included in our analyses (See figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…We included eleven qualitative studies [40], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62] and 27 quantitative studies [7], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [63], reporting 31 independent studies. One study [40] included both qualitative and quantitative study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, in our study, nearly half of the women with menopause were not advised to start HT (42.3%). Similarly, some doctors in the USA have concerns about starting and continuing HT due to cancer risks 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, infertility treatment implementing in vitro fertilization (IVF) involves controlled ovarian hyperstimulation (COH) in which combinations of gonadotropin hormones, follicle-stimulating hormone (FSH), luteinizing hormone (LH), and human chorionic gonadotropin (hCG), are used to stimulate follicle growth, steroid hormone production, oocyte maturation, and ovulation. When results from the Women’s Health Initiative (WHI) study suggested that hormone replacement therapy may increase the risk for breast cancer in 2002, concern was raised for both patients and physicians regarding the use of hormone therapies, not only during menopause, but also for oral contraception and infertility treatment (4,5). The impact of infertility regimens on breast cancer risk is largely unknown, with some studies suggesting a possible correlation while others have found no definitive association (610).…”
Section: Introductionmentioning
confidence: 99%